Malnutrition and Poor Physical Function Are Associated With Higher Comorbidity Index in Hospitalized Older Adults - Amasene, Maria; Medrano, María; Echeverria, Iñaki; Urquiza, Miriam; Rodriguez-Larrad, Ana; Diez, Amaia; Labayen, Idoia; Ariadna, Besga-Basterra (Frontiers in Nutrition, 2022)
Background: Charlson Comorbidity Index (CCI) is the most widely used method to measure comorbidity and predict mortality. There is no evidence whether malnutrition and/or poor physical function are associated with higher CCI in hospitalized patients. Therefore, this study aimed to (i) analyze the association between the CCI with nutritional status and with physical function of hospitalized older adults, and (ii) to examine the individual and combined associations of nutritional status and physical function of older inpatients with comorbidity risk. Methods: A total of 597 hospitalized older adults (84.3±6.8 years, 50.3% women) were assessed for CCI, nutritional status (the Mini Nutritional Assessment-Short Form, MNA-SF) and physical function (handgrip strength and the Short Physical Performance Battery). Results: Better nutritional status (p<0.05) and performance within handgrip strength and the SPPB were significantly associated with lower CCI score among both males (p<0.005) and females (p<0.001). Patients with malnutrition or risk of malnutrition (OR: 2.165, 95% CI: 1.408-3.331, p<0.001) as well as frailty (OR: 3.918, 95% CI: 2.326-6.600, p<0.001) had significantly increased risk for being at severe risk of comorbidity. Patients at risk of malnutrition or malnourished had higher CCI score regardless of being fit or unfit according to handgrip strength (p for trend<0.05) and patients classified as frail had higher CCI despite their nutritional status (p for trend<0.001). Conclusions: The current study reinforces the use of the MNA-SF and the SPPB in geriatric hospital patients as they might help to predict poor clinical outcomes, and indirectly post-discharge mortality risk.